Model Transportasi dalam Meminimumkan Biaya Distribusi Beras Kemasan - Adoe, V S (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2021)
Rice is a strategic commodity that a very important role as the main staple food for the majority of people in Indonesia. Rice has its own distribution development pattern that provides added value to business actors. "CV. Hidup Baru Jaya" is a company in Kupang City that is engaged in distributing packaged rice from storage warehouses to several storage warehouses in other areas. In distributing the rice, the company tries to reduce or minimize the distribution costs incurred in order to obtain optimal profit. Mathematically, the transportation model is one solution that can be used to solve this rice distribution problem. By using POM-QM V4 as the optimal solution tool, it was found that the company could distribute 125 sacks of Raja Kupang rice to the Malaka Warehouse; 150 sacks of rice to Rote Warehouse, 75 sacks to Malaka Warehouse and 200 sacks to Atambua Warehouse for Stroberry rice; Nona Timor rice was 200 sacks to Semau Warehouse, 50 sacks to Rote Warehouse and 200 sacks to Sulamu Warehouse. Thus, the company profits Rp. 20,000,000, -.